Analisis Subtitusi Limbah Plastik (LDPE) terhadap Karakteristik Marshall Pada Campuran Laston AC-WC - Pribadi, Gali; Indriasari, Indriasari; Rahman, Rafi Luthfir (Jurnal Kridatama Sains dan Teknologi, 2023)
Waste which is a disposal material from production, both from nature and human activities that are not used, can cause heaps and piles of waste that some cannot be recycled, so that it can have a negative impact on society if it is not managed properly. Therefore, the authors use waste as a mixture in making laston or AC-WC. In this study used plastic waste type Low Density Polyethylene (LDPE) which is often found in the surrounding environment. The asphalt layer used is Laston Wearing Course (AC-WC) which is commonly used for high traffic levels. Variations in the levels of plastic waste used are 0%; 5%; 7.5%; 10% of the total weight of the asphalt plan. The stages in this research include the physical test of the material, checking the AC-WC specifications referring to the general specifications of Bina Marga 2018, and Marshall testing. The method used in this research is the wet method. The results of this study found the optimum asphalt content used as a mixture with the addition of LDPE plastic waste, namely 6.3% asphalt content. Marshall test results show a better level of stability than conventional asphalt. This can be proven by the results of testing using Marshall. the average stability value is 1,884,53kg. Where this value increases compared to the stability value in the mixture without the addition of LDPE which is 1,787,39 kg.Keywords: Asphalt Concrete Wearing Course, Low Density Polyethilene (LDPE), Marshall Parameters